2018
DOI: 10.1111/ctr.13297
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparities in liver transplant candidates with nonalcoholic steatohepatitis

Abstract: Women with NASH cirrhosis had a higher risk of death on the LT waiting list and were less likely to receive LT compared to men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…123 Thus, NASH women remain longer on the waiting list for transplant, are more likely to be removed, have a higher risk of death and are less likely to receive LT compared to men with NASH, even when adjusting for potential confounding covariates. As a matter of facts, when the authors compared NASH patients to HCV patients, the magnitude of sex discrepancy resulted higher in NASH patients, 124 meaning that other unknown or unintentional biases exist in organ allocation.…”
Section: Pre-transplant Workup -Assessment Of Operative Riskmentioning
confidence: 99%
“…123 Thus, NASH women remain longer on the waiting list for transplant, are more likely to be removed, have a higher risk of death and are less likely to receive LT compared to men with NASH, even when adjusting for potential confounding covariates. As a matter of facts, when the authors compared NASH patients to HCV patients, the magnitude of sex discrepancy resulted higher in NASH patients, 124 meaning that other unknown or unintentional biases exist in organ allocation.…”
Section: Pre-transplant Workup -Assessment Of Operative Riskmentioning
confidence: 99%
“…However, this study was based on ICD-9 diagnosis code, whose ability to capture NAFLD-related diagnosis and complications is severely limited. Meanwhile, in a population of 76,149 patients listed for liver transplant between 2005 and 2012 of whom 7.2% were listed for NASH, Loy et al found that women with NASH cirrhosis had a higher risk of death on the liver transplant waiting list [42].…”
Section: Nafld-related Complications Gender/sexmentioning
confidence: 99%
“…NASH is the main cause of liver transplant among females and the second one in males, right after alcoholic liver disease [6,42], yet the US women with NASH are 19% less likely to receive a liver transplant compared to men [42].…”
Section: Nafld-related Complications Gender/sexmentioning
confidence: 99%
“…As a result, women were 50% more likely to be listed for NASH cirrhosis however men were more likely to be transplanted for NASH (64.3% vs 52.4%, P < 0.001). Women were more likely to experience alternate outcomes including remaining on the waitlist without LT (13.3% vs 10.6%, P = 0.006), death on the waitlist (17.1% vs. 11.4%, P < 0.001) and removal from the waitlist due to clinical deterioration (12.7% vs 10.6%, P = 0.04)[ 24 ]. Given the expected rise in NASH as the leading cause of OLT, this gender/sex-based disparity will only worsen.…”
Section: Introductionmentioning
confidence: 99%